Synthesis of fuzzy sliding mode controller for liquid level control in spherical tank. Issue 1 (31st December 2016) - Sreepradha, C.; Deepa, P.; Panda, Rames C.; Manamali, M.; Shivakumar, R.
Abstract: Spherical tanks are often used in process industries as storage or surge tank where control of level is essential. The liquid level in the spherical tank is modeled using first principle technique. A sliding mode controller (SMC) is designed initially to get the information of the stable closed loop process. Fuzzy-based SMC controller is developed by collecting the sliding surface data to reduce the chattering effect caused by SMC and to get the smooth sliding surface. The designed controller can drive the system states to the boundary layer. The performance of the proposed controller is compared with IMC based PI controller and the SMC. Proposed controller performance is encouraging and can be suggested for implementation in controlling the liquid level in spherical geometry.